An Ethnoastronomy Learning Progression (eALP): Scientific Literacy Skills As The Progress Dimensions - Muslimah Susilayati; Wahyu Hardyanto; Supriyadi Supriyadi; Arif Widiyatmoko (Universitas Negeri Semarang, 2022)
Abstrak. Astronomy which studies natural phenomena related to the motion of celestial bodies is one of the study materials that undergraduates in science education need to master. In this digital era, to study the relative motion of celestial bodies observed from the earth, various skills are needed and supported by the right technology. The author proposes scientific literacy skills as a dimension of progress in the ethnoastronomy learning progression of the earth's seasons for the science program undergraduate program. Scientific literacy skills have three dimensions, namely scientific concepts, scientific process, and scientific context. Scientific concepts are needed to understand the phenomenon of changing seasons on earth with the support of the Stellarium application. Scientific processes are centered on the ability to obtain, interpret, and act on evidence of the phenomenon of changing seasons on earth in five scientific processes, namely recognizing scientific questions, identifying evidence, drawing conclusions, communicating conclusions, and demonstrating scientific understanding. Scientific context can be bridged through ethnoastronomy related to seasonal changes by studying the regional calendar/student residence, for example, Pranatamangsa. Students' astronomical learning progress can be defined by the increasing sophistication of their scientific literacy skills. An ethnoastronomical learning progression (eALP) framework has been developed and discussed in this paper.